2016
DOI: 10.1159/000445826
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Cyst in the Scrotum Successfully Treated while Preserving the Testis: A Case Report

Abstract: A 66-year-old male was referred to our hospital for further examination of a scrotal mass. Because of the risk of testicular cancer, we first clamped the vessels as a course of higher orchiectomy. Then, we approached the tumor through the scrotum and successfully resected it while preserving the testis. A histopathological diagnosis revealed an epidermal cyst. We herein report a rare case of an intrascrotal epidermal cyst successfully treated while preserving the testis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…On MRI, testicular epidermal cysts are described as high-intensity, well-defined solid masses surrounded by a low-signal capsule on T2-weighted imaging [17]. Langer et al [18] and Kondo et al [19] showed that on T 1 -weighted MR images, some lesionshad low signal-based, center with spotty high signal ("target" sign) and on T 2 -weighted MRI, some lesions had a laminated appearance, with alternating low and high signal intensity areas ("onion skin" sign). Although MRI is not routinely performed in our practice, we found the same findings in one patient.…”
Section: Discussionmentioning
confidence: 99%
“…On MRI, testicular epidermal cysts are described as high-intensity, well-defined solid masses surrounded by a low-signal capsule on T2-weighted imaging [17]. Langer et al [18] and Kondo et al [19] showed that on T 1 -weighted MR images, some lesionshad low signal-based, center with spotty high signal ("target" sign) and on T 2 -weighted MRI, some lesions had a laminated appearance, with alternating low and high signal intensity areas ("onion skin" sign). Although MRI is not routinely performed in our practice, we found the same findings in one patient.…”
Section: Discussionmentioning
confidence: 99%